NALAR EKOFEMINISME DALAM PEMIKIRAN HUKUM WARIS M. QURAISH SHIHAB - Umar Ali; Ridho Ridho (STIT Sunan Giri Bima, 2021)
The focus of the study in this paper is M. Quraish Shihab's thoughts in the field of inheritance law. M. Quraish Shihab's (hereinafter referred to as Shihab) thought deserves to be appointed as a target study in relation to his views on gender equality. In various published writings, especially in his book entitled